Quality-by-Design Approach and Optimization of Risk Factors by Box-Behnken Design in Formulation Development of Aspirin and Glycine Orally Disintegrating Tablet - Kayesh, R.; Bhuiya, M. R. H.; Islam, M. F.; Chowdhury, J. A. (Journal of Scientific Research, 2021)
Quality-by-design approach (QbD) was applied to develop an orally disintegrating tablet (ODT) formulation of aspirin and glycine. At first, the target quality profile and critical quality attributes (CQAs) of the product were identified. Risk assessment was accomplished by failure mode and effects analysis (FMEA) method to assess the factors having a significant effect on CQAs like disintegration time (DT), friability and assay of aspirin and glycine. Low substituted hydroxypropyl cellulose (L-HPC), croscarmellose sodium (CCS) and punch-diameter were found critical for DT and friability. The box-Behnken design was applied to optimize those 3 factors to reach a target DT of ≤ 30 sec. It was found that a punch-diameter between 8.7 ~ 9.3 mm, CCS in a range of 4 % ~ 5 %, and L-HPC in a range of 2 % ~ 8 % produced the best oral disintegrating property and reduced the risk. In summary, this work represented an excellent example of the application of QbD approach in ODT formulation development.